Hypomagnesemia, Hypocalcemia, and Tubulointerstitial Nephropathy Caused by Claudin-16 Autoantibodies. Issue 7 (July 2022) - Figueres, Lucile; Bruneau, Sarah; Prot-Bertoye, Caroline; Brideau, Gaëlle; Néel, Mélanie; Griveau, Camille; Cheval, Lydie; Bignon, Yohan; Dimitrov, Jordan; Dejoie, Thomas; Ville, Simon; Kandel-Aznar, Christine; et al.
Significant Statement: Chronic hypomagnesemia is commonly due to diarrhea, alcoholism, and drugs; more rarely, genetic defects in the effectors of renal magnesium reabsorption are responsible. The authors report on an adult patient with acquired severe hypomagnesemia, hypocalcemia, and tubulointerstitial nephropathy, with rapidly progressing kidney injury. In in vivo and in vitro studies, they found evidence of a causal link between the patient's condition and autoantibodies against claudin-16, a transmembrane paracellular protein involved in renal magnesium absorption. The patient was subsequently diagnosed with a renal carcinoma that expressed a high level of claudin-16 mRNA. Pathogenic claudin-16 autoantibodies represent a novel autoimmune cause of specific renal tubular transport disturbances and tubulointerstitial nephropathy. Screening for autoantibodies targeting claudin-16 and potentially other renal magnesium transporters or channels may be warranted in patients with acquired unexplained hypomagnesemia. Visual Abstract: Abstract : Background: Chronic hypomagnesemia is commonly due to diarrhea, alcoholism, and drugs. More rarely, it is caused by genetic defects in the effectors of renal magnesium reabsorption. Methods: In an adult patient with acquired severe hypomagnesemia, hypocalcemia, tubulointerstitial nephropathy, and rapidly progressing kidney injury, similarities between the patient's presentation and features of genetic disorders of renal magnesium transport prompted us to investigate whether the patient had an acquired autoimmune cause of renal magnesium wasting. To determine if the patient's condition might be explained by autoantibodies directed against claudin-16 or claudin-19, transmembrane paracellular proteins involved in renal magnesium absorption, we conducted experiments with claudin knockout mice and transfected mouse kidney cells expressing human claudin-16 or claudin-19. We also examined effects on renal magnesium handling in rats given intravenous injections of IgG purified from sera from the patient or controls. Results: Experiments with the knockout mice and in vitro transfected cells demonstrated that hypomagnesemia in the patient was causally linked to autoantibodies directed against claudin-16, which controls paracellular magnesium reabsorption in the thick ascending limb of Henle's loop. Intravenous injection of IgG purified from the patient's serum induced a marked urinary waste of magnesium in rats. Immunosuppressive treatment combining plasma exchange and rituximab was associated with improvement in the patient's GFR, but hypomagnesemia persisted. The patient was subsequently diagnosed with a renal carcinoma that expressed a high level of claudin-16 mRNA. Conclusions: Pathogenic claudin-16 autoantibodies represent a novel autoimmune cause of specific renal tubular transport disturbances and tubulointerstitial nephropathy. Screening for autoantibodies targeting claudin-16, and potentially other magnesium transporters or channels in the kidney, may be warranted in patients with acquired unexplained hypomagnesemia.